'Lovely beyond Words': Beckett, Value, Critique. Issue 1 (April 2017) - McDonald, Rónán
Abstract : In recent years there have been numerous pronouncements by diverse figures in the humanities, including Bruno Latour, Rita Felski and Eve Kosofsky Sedgwick, that critique and 'paranoid reading' has run out of steam. There has been renewed attention to form, the 'literary', affect and the phenomenology of reading. What are the implications of this new turn for Beckett studies? Is it possible to articulate a positive value for a writer that undoes value, without simply recuperating him or her into the cultural economy? This essay is in two parts, counterpointed but complementary. The first takes a metacritical approach, elaborating synergies in Beckett and wider developments in academic literary studies. The second offers a close reading of Beckett's late prose text 'All Strange Away', from which I derive my titular quotation. This late work is both deeply engaged with and explicitly resistant to the Western aesthetic tradition, especially Romanticism. It deploys cultural and literary traces of aesthetic tradition, but only to parody and deface them, leaving for instance the imagination/fancy distinction blurred and suggestive, and the whole equipment for judgment uncomfortably residual and remaindered. Yet for all the play on auto-critique and self-cancellation, the text keeps the imagination flickering, precisely in the self-reflexive domain. The imagined death of the imagination, endures as the remainder, preventing the actual death and thereby keeping the possibility of valuation in process. We begin to find it in the percussive accompaniment enacted by the language: the unmistakable cadences and symmetries of Beckett's own prose. Ultimately a close reading of Beckett reveals the patterns and shapes of the prose and the drama, which as Adorno pointed out, gesture towards emancipatory possibilities without naming them. The pleasure of reading Beckett emerges from the dialectic of estrangement and recognition, mixing the uncanny and patterned linguistic markers. These signposts are found in the language, in the rhythms, patterns, repetitions and variations highlighted by a formalist criticism attentive to the phenomenology of reading.